Respuesta :
Equations can be solved in one or more steps
When the solution of an equation involves two steps, then the equation is a two-step equation.
However, if the solution involves three steps, then such equation is a three-step equation.
Two-step equation
From the question, we have:
[tex]3x + (-5) = 19[/tex]
Transform the above equation to a three-step equation using the following steps:
[tex]3x + (-5) = 19[/tex]
Rewrite the expression without the brackets
[tex]3x - 5 = 19[/tex]
Collect and evaluate like terms
[tex]3x = 24[/tex]
Solve for x
[tex]x = 8[/tex]
Another way to transform the equation is as follows:
[tex]3x + (-5) = 19[/tex]
Collect like terms
[tex]3x = 19+5[/tex]
Add 19 and 15
[tex]3x = 24[/tex]
Solve for x
[tex]x = 8[/tex]
Three-step equation
An example of this type of equation is:
[tex]4(x + 2) = 4[/tex]
Start by opening the brackets
[tex]4x + 8 = 4[/tex]
Collect and evaluate like terms
[tex]4x = -4[/tex]
Solve for x
[tex]x = -1[/tex]
Read more about equations at:
https://brainly.com/question/26119747